Epoxidized Palm Oil Plasticized Polycaprolactone Nanocomposites Preparation - Emad Abbas Jaffar Al-Mulla; Fayq Hsan Jabbar; Zaidoon Jawad Kadhim; Ali Abdulabbas Abdullah; Ahmed Ghanim Wadday; Sabah Mohammed Mlkat (Nano Biomedicine and Engineering, 2017)
As alternatives to petroleum-based polymeric materials, biodegradable polymers, such as polycaprolactone has attracted a lot of attention in the scientific community due to a rapid growth of intensive interest in the global environment. Chalcone, hexadecylamine and tetradecylamine were used as one of the organic compounds to modify natural montmorillonite clay. The clay modification was carried out by stirring the clay particles in an aqueous solution of chalcone-montmorillonite, hexadecylamine-montmorillonite and tetradecylamine-montmorillonite increasing from 1.29 to 1.53, 1.59 and 1.79 nm, respectively. The modified clay was then used in the preparation of the polycaprolactone/epoxidized palm oil blend nanocomposites. They were prepared by incorporating 0.5-5% of chalcone-montmorillonite, hexadecylamine-montmorillonite and tetradecylamine-montmorillonite. The interaction of the modifier in the clay layer was characterized by X-ray diffraction and transmission electron microscopy. The nanocomposites were synthesized by solution casting of the modified clay and a polycaprolactone/epoxidized palm oil blend at the weight ratio of 80/20, which had the highest increase in the tensile strength of the blend. The X-ray diffraction and transmission electron microscopy results confirmed the production of nanocomposites. The results also showed higher thermal stability for nanocomposites compared to those of the polycaprolactone/epoxidized palm oil blend.